Does the Quality of Service affect the Loyalty of Sharia Hotel Guests? - Juliana juliana; Haiqal Darmawan; Agus Rahayu; Nispia Asya’bani; Tatang Hidayat; El Islam Purnama (Islamic Research, 2023)
The purpose of this study was to show the effect of service quality on the loyalty of sharia hotel guests in the city of Bandung. The method used in this study is a quantitative method with a research sample of 110 respondents. The data analysis technique used is linear regression with SPSS software version 22. Based on the results of linear regression analysis, this study shows that service quality has a significant effect on the loyalty of sharia hotel guests in the city of Bandung. The implication of this study shows that the service quality variable has a direct effect on increasing the loyalty of sharia hotel guests in the city of Bandung. However, this study implies the need for better service quality in sharia hotels, especially in the comfort aspect. This research is expected to provide benefits for sharia-based lodging service business actors to be able to continue to improve their service quality strategy.